Potency of Bone Marrow-Derived Mesenchymal Stem Cells and Indomethacin in Complete Freund's Adjuvant-Induced Arthritic Rats: Roles of TNF-α, IL-10, iNOS, MMP-9, and TGF-β1 - Eman A. Ahmed; Osama M. Ahmed; Hanaa I. Fahim; Tarek M. Ali; Basem H. Elesawy; Mohamed B. Ashour (Hindawi Limited, 2021)
Rheumatoid arthritis (RA) is an autoimmune syndrome affecting joint spaces, leading to the disabled state. Currently, there is no optimal therapy for RA except for systemic immunosuppressants that have variable undesirable effects after long-term use. Hence, the need for other treatment modalities has emerged in an attempt to develop a treating agent that is effective but without bad effects. Bone marrow-derived mesenchymal stem cells (BM-MSCs) may be an alternative medicine since they may differentiate into a variety of mesenchymal tissues including bone and cartilage. Indomethacin (IMC) could be suggested as an analgesic, anti-inflammatory, and antirheumatic potential agent against the course of RA since it possesses significant palliative effects and antipyretic properties. Therefore, our target of this study was to explore and compare the effect of BM-MSCs (1×106 cells/rat at the 1st, 6th, 12th, and 18th days) and IMC (2 mg/kg b.w./day for 3 weeks) either alone or in combination on arthritic rats. The model of rheumatoid arthritis in rats was induced by subcutaneous injection of 0.1 mL/rat CFA into the footpad of the right hind paw. The BM-MSC intravenous injection and IMC oral administration significantly reduced the elevated right hind leg paw diameter and circumference, serum anti-CCP, and ankle joint articular tissue expressions of TNF-α, iNOS, MMP-9, and TGF-β1 while they significantly increased the lowered articular IL-10 expression in CFA-induced arthritic rats. The combinatory effect of the two treatments was the most potent. In conclusion, the treatment of RA with BM-MSCs and IMC together is more effective than the treatment with either BM-MSCs or IMC. The Th1 cytokine (TNF-α), Th2 cytokine (IL-10), iNOS, MMP-9, and TGF-β1 are important targets for mediating the antiarthritic effects of BM-MSCs and IMC in CFA-induced arthritis in rats.